2015
DOI: 10.1007/s00330-015-3765-5
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of epicardial fat volume measurements by computed tomography: a systematic review of the literature

Abstract: Objectives To perform a systematic review of the growing body of literature evaluating the prognostic value of epicardial fat volume (EFV) quantified by cross-sectional imaging for adverse clinical outcomes. Methods Two independent reviewers performed systematic searches on both PubMed and Scopus using search terms developed with a medical librarian. Peer-reviewed articles were selected based on the inclusion of outcome data, utilization of epicardial fat volume and sufficient reporting for analysis. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 32 publications
2
36
0
6
Order By: Relevance
“…32 To our knowledge, no report has evaluated the cutoff value of the EATV for predicting the development of AF. 33 Shmilovich et al evaluated the threshold for the upper normal limit of the EATVI measured on non-contrast cardiac CT; the 95th-percentile definition of the upper normal limit of the EATVI was 68 mL/m 2 (equivalent to EATV of 125 mL), and this value can be an independent predictor (OR, 2.8; 95% confidence interval, 1.3-6.4, P=0.012) of major adverse cardiovascular events (MACEs) consisting of cardiovascular death, myocardial infarction, stroke, and percutaneous or surgical coronary artery revascularization. 34 Interestingly, the cutoff values of the EATVI in the study by Shmilovich et al 34 for MACEs and in the current study for PAF and PeAF are comparable.…”
Section: Longitudinal Changes In Eatvi In Subjects With Sr Paf and Peafmentioning
confidence: 99%
“…32 To our knowledge, no report has evaluated the cutoff value of the EATV for predicting the development of AF. 33 Shmilovich et al evaluated the threshold for the upper normal limit of the EATVI measured on non-contrast cardiac CT; the 95th-percentile definition of the upper normal limit of the EATVI was 68 mL/m 2 (equivalent to EATV of 125 mL), and this value can be an independent predictor (OR, 2.8; 95% confidence interval, 1.3-6.4, P=0.012) of major adverse cardiovascular events (MACEs) consisting of cardiovascular death, myocardial infarction, stroke, and percutaneous or surgical coronary artery revascularization. 34 Interestingly, the cutoff values of the EATVI in the study by Shmilovich et al 34 for MACEs and in the current study for PAF and PeAF are comparable.…”
Section: Longitudinal Changes In Eatvi In Subjects With Sr Paf and Peafmentioning
confidence: 99%
“…Epicardial adipose tissue (EAT) is a fat depot that is emerging as a novel marker of subclinical cardiovascular disease, and, like CAC score, it can be derived from non-contrast cardiac computed tomography (CT). Several studies have demonstrated that EAT provides incremental prognostic information over and above CAC and traditional risk factors for the prediction of major adverse cardiac events [17, 18]. EAT is unique to other fat depots in the body in that it may exert proatherogenic effects on the coronary arteries through local inflammatory mediators and infiltration of inflammatory cells [1924].…”
Section: Introductionmentioning
confidence: 99%
“…It is postulated that close proximity of the increased EAT to the heart and vessels (14) and the lack of a physical barrier between these structures allow for diffusion of proinflammatory cytokines that could play role in the development of cardiometabolic diseases (14–16). Computed tomography (CT) is a reliable and reproducible method for quantification of epicardial fat volume (EFV) (17) independent of cardiac cycle phase (18). Unlike CT, echocardiography can only measure EAT thickness as a one-dimensional measure (16).…”
Section: Introductionmentioning
confidence: 99%